Ethical Use of Lifelogging Data for Research: Perceived Value and Privacy Concerns of Wearable Camera Users - Yoon, Ayoung; Jones, Kyle M.L.; Spotts, Lydia (Nordisk Tidsskrift for Informationsvidenskab og Kulturformidling, 2017)
Video data generated from wearable cameras is now available online, as the concept of “lifelogging” has been introduced to many citizens due to the spread of wearable camera equipment. Usually, these wearable cameras automatically capture images or record videos from a first-person point of view; they collect a new form of information that cannot be captured through other means. Citizen data Harvest in Motion Everywhere (CHIME) project pays close attention to the value of this new type of resource, particularly regarding the video data that cyclists record using wearable cameras over a long period of time. These contextually rich data capture community members’ infrastructure experiences and interactions with other transit modes, as well as environmental changes. If curated and made publicly accessible, there is great potential for various stakeholders, including public historians, researchers, city planners, and citizens, to use the data. However, making these videos open to the public and to researchers raises ethics issues, as the data include sensitive, location-based information that may intrude into private lives. Additionally, the videos include the accidental collection of data from secondary participants (bystanders). In this paper, we will describe the potential value of citizen-generated video data using the CHIME project example and discuss the privacy and ethical considerations related to the use of this type of data for scientific and citizen research.